2023
DOI: 10.1096/fj.202301591rr
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cutaneous heat‐sensitive Ca2+‐permeable transient receptor potential vanilloid 3 channels alleviates UVB‐induced skin lesions in mice

Yaxuan Qu,
Xiaoying Sun,
Ningning Wei
et al.

Abstract: Ultraviolet B (UVB) radiation causes skin injury by trigging excessive calcium influx and signaling cascades in the skin keratinocytes. The heat‐sensitive Ca2+‐permeable transient receptor potential vanilloid 3 (TRPV3) channels robustly expressed in the keratinocytes play an important role in skin barrier formation and wound healing. Here, we report that inhibition of cutaneous TRPV3 alleviates UVB radiation‐induced skin lesions. In mouse models of ear swelling and dorsal skin injury induced by a single exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Another study confirmed these facts by using two antagonists applied topically on the sore dorsal skin or swollen ear in KO mouse, which resulted in a dose-dependent reduction in inflammation [72].…”
Section: Trpv Role In Wound Healingmentioning
confidence: 75%
“…Another study confirmed these facts by using two antagonists applied topically on the sore dorsal skin or swollen ear in KO mouse, which resulted in a dose-dependent reduction in inflammation [72].…”
Section: Trpv Role In Wound Healingmentioning
confidence: 75%
“…Another study confirmed these facts by using two antagonists applied topically on the sore dorsal skin or swollen ear in KO mouse, which resulted in a dose-dependent reduction in inflammation [ 79 ].…”
Section: Topics In Wound Healingmentioning
confidence: 92%